IMPLEMENTASI LEARNING TRAJECTORY KALKULUS BERBASIS REALISTIC MATHEMATICS EDUCATION UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR MATEMATIS TINGKAT TINGGI SISWA SMA KOTA PADANG - Arnellis, Suherman, Nonong Amalita (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Development of Learning Trajectories (LT) is the development of learning pathways in calculus material that can improve high-order thinking skills (HOTS). Students have difficulty working on Calculus questions, because they do not understand their meaning in everyday life. The purpose of this study is to implement Learning Trajectories that have been produced in HOTS-based Calculus material with the Realistic Mathematics Education (RME) approach. As in the previous research, the stages of research included literature studies on LT, HOTS, and RME, and carried out the design effectiveness of the LT. The results of the LT design that are valid and practical are then measured and assessed to determine the effectiveness of the data obtained concluded that the learning trajectory of topic function calculus at the trial stage sees effectiveness as an effective category. Proven at the stage of implementation, motivation emerged positive attitudes such as active, happy, and enthusiastic students taking lessons. This is proven by the value of the test of high-level thinking ability of students found the average value of the experimental class test post is greater than the average value of the control class after being given treatment.